Cost Management for Scientific research by an industrial Enterprise - I. E. Mizikovskii (Учёт. Анализ. Аудит, 2022)
The paper describes the issues of improving the existing methods and ways of structuring the information and instrumental space for making managerial decisions in scientific research (R&D) by industrial enterprises on their own. The model for managing the resources involved in this has a complex, ambivalent nature, since excessive savings can play a negative role in the results of research, however, in conditions of effective management, a complete absence of control over the state of costs by the subject of management is impossible. The way out of this ambiguous situation is seen in strengthening the verification of information entering the data processing system, as well as in incorporating into the considered information and instrumental space management accounting tools related to rationing, budget planning (budgeting), quantifying costs and calculating the cost of work by the direct costing method. The study goal is to develop an IIP that meets effective management requirements, capable of generating information relevant to situation-oriented, systemic and strategic types of decisions. The theoretical and methodological base is made up of process, system and operation-oriented types of scientific methods. Existing approaches to analytical cost accounting, verification of primary information, planning, standardization and accounting activities of industrial enterprises in the field of research and development are considered in detail. The introduction of the information and instrumental space of the proposed configuration into the management practice of the enterprise will allow, when conducting research, to significantly reduce the costs of persons responsible for the final business result, for searching and processing data, increase the reliability of the information fund and the quality of decisions made, optimize the cost estimate and accounting work.